2016
DOI: 10.1002/cplu.201600389
|View full text |Cite
|
Sign up to set email alerts
|

Application of γ‐Valerolactone as an Alternative Biomass‐Based Medium for Aminocarbonylation Reactions

Abstract: γ‐Valerolactone (GVL) was proposed as a renewable, nontoxic reaction medium with negligible vapor pressure for homogeneous Pd‐catalyzed aminocarbonylation reactions. Iodobenzene as a model substrate and its 4‐substituted derivatives were converted to the corresponding 2‐ketocarboxamides with high conversions and chemoselectivities in γ‐valerolactone. The effect of carbon monoxide pressure and reaction temperature on the conversion and selectivities were studied in the range 1–50 bar and 25–100 °C, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 67 publications
(39 reference statements)
0
22
0
Order By: Relevance
“…[22][23][24] GVL has thus been considered as one of the most important platform chemicals available in future lignocellulosic biorefineries. GVL possesses excellent solvent properties (e.g., solvation) for homogeneous and heterogeneous catalysis, [25][26][27][28][29][30][31][32][33][34][35] but it may also serve as stable and non-toxic platform chemical to be converted to a wide range of other useful chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] GVL has thus been considered as one of the most important platform chemicals available in future lignocellulosic biorefineries. GVL possesses excellent solvent properties (e.g., solvation) for homogeneous and heterogeneous catalysis, [25][26][27][28][29][30][31][32][33][34][35] but it may also serve as stable and non-toxic platform chemical to be converted to a wide range of other useful chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…GVL can also be successfully utilized as a reaction medium for the homogeneous Pt-(Scheme 15) and Rh-catalyzed enantioselective hydroformylation of styrene, 67,68 as well as the Pd-catalyzed aminocarbonylation (Scheme 16) of iodoaromatic compounds. 69 In general, slightly lower activities were observed in GVL compared to in conventional organic solvents, however, the selectivities were similar, allowing its application as an alternative reaction environment. For heterogeneous catalysis, Vaccaro and co-workers demonstrated that synthetically important coupling reactions such as the Heck, 70 Sonogashira-, 71 Hiyama-, 72 and Catellani-reactions (Scheme 17) 73 could be suc-cessfully performed in GVL.…”
Section: Safer Solventsmentioning
confidence: 95%
“…34 Due to its physicochemical properties, GVL has found widespread applications as an alternative to hazardous organic solvents in transition metal-catalyzed transformations, including cross-coupling reactions, 35 hydroformylations 36 and aminocarbonylations. 37 In contrast, step-economical catalyzed C-H activations in renewable biomass derived solvent GVL have only recently been developed.…”
Section: γ-Valerolactone (Gvl)mentioning
confidence: 99%